Conservation resource allocation, small population resiliency, and the fallacy of conservation triage. Issue 5 (4th May 2021) - Wiedenfeld, David A.; Alberts, Allison C.; Angulo, Ariadne; Bennett, Elizabeth L.; Byers, Onnie; Contreras‐MacBeath, Topiltzin; Drummond, Gláucia; da Fonseca, Gustavo A. B.; Gascon, Claude; Harrison, Ian; Heard, Nicolas; Hochkirch, Axel; et al.
Abstract: Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss. Abstract : Article impact statement : Conservation triage is not necessary for species conservation. Adequate resources exist; even species with small populations can recover. Abstract : Asignación de Recursos para la Conservación, Resiliencia de Poblaciones Pequeñas y la Falacia del Triaje de Conservación Resumen: Algunos métodos de priorización de la conservación están basados en el supuesto de que las necesidades de la conservación superan a los actuales recursos y que no todas las especies pueden ser conservadas; por lo tanto, se necesita un esquema de triaje (esto es, cuando el sistema está abrumado, las especies deben dividirse en tres grupos con base en su probabilidad de supervivencia y los esfuerzos deben enfocarse en aquellas especies dentro del grupo con las mejores probabilidades de supervivencia y a aquellas en el grupo sin probabilidades de supervivencia o aquellas en el grupo que no necesita esfuerzos especializados para su conservación se les deben reducir o negar los esfuerzos de conservación) para dirigir la asignación de recursos. Discutimos que esta estrategia para la toma de decisiones no es apropiada porque los recursos no están tan limitados como se asume con frecuencia y tampoco es evidente que existan especies que no puedan ser conservadas. Por ejemplo, tan sólo un tamaño poblacional pequeño no es suficiente para condenar a una especie a la extinción; contamos con ejemplos en plantas, reptiles, aves y mamíferos. Aunque actualmente todos los recursos dedicados a la conservación de todas las especies amenazadas son insuficientes, los recursos económicos mundiales son vastos y se podrían dedicar mayores recursos a la conservación de especies. El marco de trabajo político para la conservación de especies ha mejorado, con iniciativas como los Objetivos de Desarrollo Sustentable de la ONU y otros acuerdos internacionales, el financiamiento de mecanismos como el Fondo para el Medio Ambiente Mundial, y el surgimiento de muchas organizaciones no gubernamentales mediante programas de subsidios pequeños hábiles y de respuesta rápida. Para que un sistema de priorización no permita las extinciones, las cero extinciones deben ser un objetivo explícito del sistema. La extinción no es inevitable y no debería ser aceptable. El objetivo de cero extinciones inducidas por humanos es imperativo dada la irreversibilidad de la pérdida de especies.